Modelling of OpenFlow‐based software‐defined networks: the multiple node case. Issue 5 (1st September 2015) - Mahmood, Kashif; Chilwan, Ameen; Østerbø, Olav; Jarschel, Michael
Abstract : OpenFlow (OF) is one of the most widely used protocols for controller‐to‐switch communication in a software defined network (SDN). Performance analysis of OF‐based SDN using analytical models is both highly desirable and challenging. There already exists a very elegant analytical model based on M/M/1 queues to estimate the packet sojourn time and probability of lost packets for the case in which a controller is responsible for only a single node in the data plane. However the literature falls short when it comes to the multiple node case, i.e. when there is more than one node in the data plane. In this work we propose a model to address this challenge by approximating the data plane as an open Jackson network with the controller also modeled as an M/M/1 queue. The model is then used to evaluate the system in the light of some of the metrics, such as; how much time a packet spends on average in an OF‐based network and how much data we can pump into the network given the average delay requirements. Finally the PDF and the CDF of the time spent by the packet in an OF‐based SDN for a given path is derived.